Vibration Control of a Semiactive Vehicle Suspension System Based on Extended State Observer Techniques. (19th May 2014) - Zhang, Ze; Karimi, Hamid Reza; Huang, Hai; Robbersmyr, Kjell G.
Abstract : A feedback control method based on an extended state observer (ESO) method is implemented to vibration reduction in a typical semiactive suspension (SAS) system using a magnetorheological (MR) damper as actuator. By considering the dynamic equations of the SAS system and the MR damper model, an active disturbance rejection control (ADRC) is designed based on the ESO. Numerical simulation and real-time experiments are carried out with similar vibration disturbances. Both the simulation and experimental results illustrate the effectiveness of the proposed controller in vibration suppression for a SAS system.